Nonmigrating Equivalent Substitutes for PVC/DOP Formulations as Shown by a TG Study of PVC with Covalently Bound PEO-PPO Oligomers - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2017)
Monoamino functionalized ethylenoxide (EO)/propylenoxide oligomers (Jeffamine) are linked chemically to poly(vinyl chloride) (PVC) using trichlorotriazine chemistry in order to prepare nonmigrating internally plasticized materials. The dependence of the plasticizer efficiency on both the number of anchoring points to the chains and the PVC/plasticizer compatibility is investigated using oligomers of different molecular weight and hydrophilic-hydrophobic balance. Hydrophilic oligomers (containing predominantly EO) of molecular weights between 2000 and 5000 g mol(-1) exhibit excellent plasticizer efficiency, nearly identical to di-2-ethylhexylphthalate (DOP) in conventional PVC/DOP mixtures and may therefore be used as nonmigrating equivalents for DOP.
Keywords: aliphatic polyethers; covalent binding; glass transition temperature; mechanical properties; plasticizer efficiency; PVC; PLASTICIZERS; MIGRATION; CHEMISTRY